(untitled) (Canadian Journal of Native Studies, 2026)
Indigenous Territories (IT) are increasingly viewed as important assets in the context of climate change and erosion of biodiversity. In Brazil however, they are currently under intense pressure under the pretext of development. Comparing with the situation of the United States is a good benchmark for what might come to Brazil. In this perspective, we first present the historical processes that led to the recognition of IT, then contrast the structure of IT in both countries from a juridical, administrative and geographical point of view, and finally point out how issues related to economic development play out in both cases.